A Search For New Dwarf Galaxies Outside The Nearby Groups - Karachentsev, I. D.; Karachentseva, V. E.; Kaisin, S. S.; Kaisina, E. I. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We undertook a search for new nearby dwarf galaxies outside the known groups in the Local Volume using the data on DESI Legacy Imaging Surveys. In a wide sky area of ~5000 square degrees directed toward the Local Void, we found only 12 candidates to nearby low mass galaxies. Almost all of them are classified as irregular or transition type dwarfs. Additionally, we examined areas of the sky exposed with the Hyper Suprime Camera of the Subaru telescope (~700 square degrees) and found nine more candidates to nearby dwarfs. Finally, nine candidates to the Local Volume were selected by us from the Zaritsky's SMUDG catalog that contains 7070 ultra-diffuse objects automatically detected in the whole area of the DESI surveys. We estimated a fraction of quiescent dSph galaxies in the general cosmic field to be less than 10 percent. Используя данные обзора DESI Legacy Imaging Surveys, мы предприняли поиск новых близких карликовых галактик вне известных групп в Местном Объеме. В обширной области неба площадью примерно 5000 квадратных градусов, направленной к Местному Войду, мы нашли только 12 кандидатов в близкие галактики низкой массы. Все они классифицированы как иррегу лярные либо карлики переходного типа. Дополнительно мы обследовали площади неба, снятые телескопом Субару с камерой Hyper Suprime Camera (около 700 кв. град.) и обнаружили еще девять кандидатов в близкие карлики. Наконец, 9 кандидатов в Местный Объем были отобраны нами из каталога Зарицкого (SMUDG), который содержит 7070 ультра-диффузных объектов, найденных автоматически на всей площади обзора DESI. Мы оцениваем долю "спокойных" dSph галактик в общем космическом поле не более 10 процентов.
Keywords: Astrophysics